High-Temperature Tribological Behavior of Nickel-Based Hardfacing Alloys. Issue 4 (25th June 2021) - Chakraborty, Gopa; Rani, Revati; Ramaseshan, R.; Davinci, M. Arvinth; Das, C. R.; Mathews, Tom; Albert, S. K.
Abstract: The friction and wear behavior of electrode rod nickel chromium (ER NiCr) nickel-based hardfacing alloys ER NiCr-A, ER NiCr-B, and ER NiCr-C deposited over austenitic stainless steel was studied against silicon carbide counter body by ball-on-disc tribotesting at 25 °C (1 bar pressure, 3 × 10 −5 mbar vacuum) and at 550 °C (3 × 10 −5 mbar vacuum) temperature. The wear tracks were examined using confocal microscope, profilometer and Raman Spectroscopy. The friction coefficient and wear rate of the deposits are correlated with the microstructure of the alloy. Wear rate of NiCr-B is found to be minimum both at ambient and elevated temperatures and can be considered as the best choice among the three alloys studied for hardfacing applications.